O enem izmed vidikov moje literarne zgodovine (s posebnim ozirom na slovensko dramatiko) - Kermauner, Taras (Slavistična revija, 2006)
The article illustrate the thesis that the author's encounters with Slovene drama and, consequently, his dealing with Slovene literary criticism originates in his direct contact with staged performances in his teen years. In these plays, the author discovered his personal fate, searches for, and came closer to the meaning of life.
Keywords: education; history of literature; literarna zgodovina; literarne študije; literary criticism; meaning; model; Slovene drama; slovenska dramatika; smisel; vzgoja; vzor